Immunomodulatory bioactive glasses for tissue regeneration - Zheng, Kai; Niu, Wen; Lei, Bo; Boccaccini, Aldo R. (Acta Biomaterialia, 2021)
The regulatory functions of the immune response in tissue healing, repair, and regeneration have been evidenced in the last decade. Immune cells play central roles in immune responses toward inducing favorable tissue regenerative processes. Modulating and controlling the immune cell responses (particularly macrophages) is an emerging approach to enhance tissue regeneration. Bioactive glasses (BGs) are multifunctional materials exhibiting osteogenic, angiogenic, and antibacterial properties, being increasingly investigated for various tissue regeneration scenarios, including bone regeneration and wound healing. On the other hand, the immunomodulatory effects of BGs in relation to regenerating tissues have started to be understood, and key knowledge is emerging. This is the first review article summarizing the immunomodulatory effects of BGs for tissue repair and regeneration. The immune response to BGs is firstly introduced, discussing potential mechanisms regarding the immunomodulation effects induced by BGs. Moreover, the interactions between the immune cells involved in the immunomodulation process and BGs (dissolution products) are summarized in detail. Particularly, a well-regulated and timely switch of macrophage phenotype from pro-inflammatory to anti-inflammatory is crucial to constructive tissue regeneration through modulating osteogenesis, osteoclastogenesis, and angiogenesis. The influence of BG characteristics on macrophage responses is discussed. We highlight the strategies employed to harness macrophage responses for enhanced tissue regeneration, including the incorporation of active ions, surface functionalization, and controlled release of immunomodulatory molecules. Finally, we conclude with our perspectives on future research challenges and directions in the emerging field of immunomodulatory BGs for tissue regeneration. Statement of significance: Immunomodulatory effects of bioactive glasses (BGs) in relation to bone regeneration and wound healing have started to be understood. We summarize those studies which have focused on immunomodulatory BGs for tissue regeneration. We first introduce the potential mechanisms of the immunomodulation effects induced by BGs. Interactions between the cells involved in immunomodulation processes and BGs (and their dissolution products, biologically active ions) are elaborated. We highlight the strategies employed to modulate macrophage responses for enhancing tissue regeneration, including incorporation of active ions, surface functionalization, and controlled release of immunomodulatory agents. This is the first review article summarizing and outlining the immunomodulatory effects of BGs for tissue regeneration. We anticipate that increasing research efforts will start to emerge in the area of immunomodulatory BGs.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Bioactive glasses; Bone tissue regeneration; Immune response; Immunomodulation; Macrophages; Wound healing